Hydroxyapatite-Based Adsorbent Materials from Aquaculture Waste for Remediation of Metal-Contaminated Waters: Investigation of Cadmium Removal - Mirco Cescon; Francesco Chiefa; Tatiana Chenet; Maura Mancinelli; Claudia Stevanin; Annalisa Martucci; Luisa Pasti (Clean Technologies, 2025)
Adsorption represents an effective strategy for water remediation applications, particularly when utilising eco-friendly materials in a circular economy framework. This approach offers significant advantages, including low cost, material availability, ease of operation, and high efficiency. Herein, the performance of cadmium ion adsorption onto hydroxyapatites, derived through a calcination-free process from shells of two mollusc species, Queen Scallop (Aequipecten opercularis) and Pacific Oyster (Magallana gigas), is examined. The phase and morphology of the synthesised adsorbents were investigated. The results showed that hydroxyapatites obtained from mollusc shells are characterised by high efficiency regarding cadmium removal from water, exhibiting rapid kinetics with equilibrium achieved within 5 min and high adsorption capacities up to 334.9 mg g−1, much higher than many waste-based adsorbents reported in literature. Structural investigation revealed the presence of Cadmium Hydrogen Phosphate Hydrate in the hydroxyapatite derived from oyster shells loaded with Cd, indicating the formation of a solid solution. This finding suggests that the material not only has the capability to decontaminate but also to immobilise and store Cd. Overall, the results indicate that hydroxyapatites prepared via a synthetic route in mild conditions from waste shells are an economical and efficient sorbent for heavy metals encountered in wastewater.